Pengaruh Motivasi Dan Pelatihan Terhadap Kinerja Karyawan PT Jaya Persada Indonesia Cabang Maxi Pasar Minggu Jakarta Selatan - Dodi Darmawan (Jurnal Ilmiah Ekonomi, Manajemen dan Bisnis, 2020)
The purpose of this study was to analyze the effect of motivation and training on the performance of employees of PT Jaya Persada Indonesia Maxi Pasar Minggu Branch South Jakarta. The research method used is quantitative research. A total of 63 employees have been selected as research respondents through sampling techniques. Quantitative data were obtained through the distribution of a 5-scale Likert questionnaire. The results of the study revealed that there was an influence of motivation and training both partially and simultaneously on the performance of employees of PT Jaya Persada Indonesia Maxi Pasar Minggu Branch, South Jakarta. This study then analyzed in more depth the contribution of influence exerted by each independent variable (motivation and training) to the dependent variable (employee performance), and the results showed a considerable contribution